Excluding pregnancy among women initiating antiretroviral therapy: efficacy of a family planning job aid - Phiri Henry; Mwema Francis; Makelele Patrick; Malebe Thierry; Kabaso Mushota; Mwenda Lona; Torpey Kwasi; Mukundu Jonathan; Weaver Mark A; Stanback John (BMC, 2010)
Abstract Background Guidelines for initiating ART recommend pregnancy testing, typically a urine test, as part of the basic laboratory package. The principal reason for this recommendation is that Efavirenz, a first-line antiretroviral medication, has the potential of causing birth defects when used in the first trimester of pregnancy and is therefore contraindicated for use by pregnant women. Unfortunately, in many African countries pregnancy tests are not routinely provided or available in ART clinics, and, when available outside clinics, are often not affordable for clients. Recently, the World Health Organization added a family planning job aid called the 'pregnancy checklist,' developed by researchers at Family Health International, as a recommended tool for screening new ART clients to exclude pregnancy. Although the checklist has been validated for excluding pregnancy among family planning clients, there are no data on its efficacy among ART clients. This study was conducted to assess the clinical performance of a job aid to exclude pregnancy among HIV positive women initiating ART. Methods Non-menstruating women eligible for ART were enrolled from 20 sites in four provinces in Zambia. The pregnancy checklist was administered followed by a urine pregnancy test as a reference standard. Sensitivity, specificity, and positive and negative predictive values were estimated. Results Of the 200 women for whom the checklist ruled out pregnancy, 198 were not pregnant, for an estimated negative predictive value of 99%. The sensitivity of the checklist was 90.0%, and specificity was 38.7%. Among the women, 416 out of 534 (77.9%) did not abstain from sex since their last menses. Only 72 out of the 534 women (13.4%) reported using reliable contraception. Among the 416 women who did not abstain, 376 (90.4%) did not use reliable contraception. Conclusion The pregnancy checklist is effective for excluding pregnancy in many women initiating ART, but its moderate sensitivity and specificity precludes its use to completely replace pregnancy testing. Its use should be encouraged in low resource settings where pregnancy tests are unavailable or must be rationed. Family planning methods should be available and integrated into ART clinics.